Pengaruh Net Interest Margin Dan Earning Per Share Terhadap Harga Saham Pada PT. Bank Central Asia (BCA) TBK Periode 2014-2023 - Ananda Hadistia; Giyarsih Giyarsih (Journal of Innovative and Creativity, 2025)
This study aims to determine the effect of Net Interest Margin (NIM) and Earning Per Share (EPS) on Stock Prices in PT. Bank Central Asia, Tbk. period 2014-2023. The Method in this research is quantitative. The population used is the entire financial statements of PT Bank Central Asia, Tbk for the period 2014-2023 and the sample used is the financial position report and income statement. The data analysis techniques used is statistical analysis with classical assumption testing, regression, correlation, determination and hypothesis testing. Based on the partial research results using the t test, the Net Interest Margin (NIM) variable has no effect on the Stock Prices with a comparison value of t count (2,272) < t table (2,365) and a significance value of 0.057 > 0.05. Earning Per Share (EPS) variable has no effect on Stock Prices with a comparison value of t count (-1.835) < t table (2.365) and a significance value of 0.109 > 0.05. The simultaneous test results show that the Net Interest Margin (NIM) and Earning Per Share (EPS) variables have no significant effect on Stock Price, the regretion equition is Y = 6,543 + 3,080X1 – 0,467X2 with the value of F count (2.867) < F table (4.74) and a significance value of 0,123 > 0,05. The value of the Determination Coefficient (R2) is 0.450.